The Iraq War and Democratic Governance - Betts, Judith. author. aut Link
XV, 236 p. 1 illus.
Keywords: ‘Drawing on an array of primary sources and interviews, The Iraq War and Democratic Governance makes a profound contribution to the field. The book’s authoritative account of the post-war inquiries and political consequences in Britain and Australia is essential reading for academics and practitioners interested in matters of international security.’ –Patrick A. Mello, Visiting Scholar, Willy Brandt School of Public, University of Erfurt, Germany This book examines the decisions by Tony Blair and John Howard to take their nations into the 2003 Iraq War, and the questions these decisions raise about democratic governance. It also explores the significance of the US alliance in UK and Australian decision-making, and the process for taking a nation to war. Relying on primary government documents and interviews, and bringing together various strands of literature that have so far been discussed in isolation (including historical accounts, party politics, prime ministerial leadership and intelligence studies), the authors provide a comprehensive and original view on the various post-war inquiries conducted in the UK, Australia. Judith Betts teaches government and political communication at the University of Technology Sydney, Australia. She has worked in the Australian Public Service, served as a ministerial adviser and as a speechwriter, and currently works as an academic. Mark Phythian is Professor of Politics in the School of History, Politics and International Relations at the University of Leicester, UK. He is the author or editor of over a dozen books, editor of the journal Intelligence and National Security, and a Fellow of the UK Academy of Social Sciences.